Agri-commerce and agroecological baseline data compilation and review - Douangsavanh, Somphasith; Phongoudome, Chansamone; Sonethavixay, Sengpachanh (International Water Management Institute, 2022)
The document provides a summary review of selected policies and policy perspectives in Laos that guide agriculture development in the country. The review looks into selected priority areas that are relevant to agro-commerce and agroecology.